Indicators for a nationwide monitoring of ecosystem services in Germany exemplified by the mitigation of soil erosion by water. (November 2018) - Syrbe, Ralf-Uwe; Schorcht, Martin; Grunewald, Karsten; Meinel, Gotthard
Highlights: Four indicators of the Ecosystem Service 'prevention against soil erosion by water' that should match into the future Europe-wide ES mapping and monitoring system are presented in detail. The results show: Ecosystems help to avoid about half a million tons soil loss by water erosion in Germany. The contribution of small landscape elements accounts for 1.1 % today. Yet, it remains a soil loss of about 45 million tons every year. As soon as comparable land use data are available, the future development will be monitored every three years. Abstract: The Biodiversity Strategy of European Union demands a nationwide assessment and mapping of ecosystem services for all member countries by 2020. In order to fulfil the task, Germany has developed an indicator set for selected ecosystem services (ES) that comprises both supply and demand indicators representing the three main categories providing, regulating and socio-cultural ES. Indicators are calculated in a way that allows them to be recalculated regularly using nationwide public data. Therefore, the method also allows for monitoring the ecosystem services and highlighting their changes. The choice of suitable indicators and their calculation for the Federal Republic of Germany is presented using the example of the ES class "mass stabilisation and control of erosion rates" and the specific ES "control of water-bound soil erosion". This service corresponds to the capacity of the ecosystems to resist the soil erosion effect caused by water. Near-natural ecosystems often resist erosion to a higher extent than areas in use, whose erosion rates depend on natural parameters and factors related to use. The actual service, and therefore the main indicator, captures the protective effect of the ecosystems against soil loss, calculated from the difference of the annual losses and the hypothetical erosion rate without vegetation. A first secondary indicator displays the already above calculated average annual loss of soil. Further secondary indicators quantify the special effects of small landscape elements and the extent of organic farming. Nationwide, the avoidance of erosion through ecosystems amounts to 467 million tons of soil per year. But the real erosion rate increases slightly, solely due to the changing crop cultivation about 7 % in three years from 2009 to 2012. The water erosion avoided by small-scale structures in the agricultural landscape accounts for 1.1 % nationwide.